Pengaruh Kualitas Pelayanan Dan Kemudahan Penggunaan Terhadap Keputusan Pembelian Melalui Kepercayaan Sebagai Variabel Mediasi Pada Konsumen Go-Food - Welsa, Henny; Cahya, Agus Dwi; Fajarningrum, Ani Rizky (Universitas Hamzanwadi, 2024)
Tight competition requires go-food to improve the purchasing decisions of its users. This study’s goal is to ascertain the extant to which service quality,usability, and trust affect consumers’ decisions to buy in go-food. The method used is quantitative, and employs a questionnaire to gather information. Respondents who came from the Gunungkidul community population whose identities were unknown amounted to 120 people using the purposive sampling technique that the researcher used. Data processing was carried out using SPSS 26. The study findings indicate that trust is positively and significantly influenced by service quality, trust is positively and significantly influenced by ease of use, service quality is positively and significantly influenced by purchasing decisions, and ease of use is positively and significantly influenced by purchasing decisions.. Based on the mediation test, the results of this study found that trust was able to mediate the influence of service quality on go-food purchasing decisions, and trust was also able to mediate the influence of ease of use on consumer purchasing decisions.